1143 Wake-up Stroke In Hispanic Veterans: Clinical Characteristics. (27th May 2020) - Colon-Feliciano, M; Prats, N; Sierra-Gonzalez, A; Jovet, G; Jimenez, L
Abstract: Introduction: Wake-up stroke (WUS) is a stroke that occurs during sleep and accounts for 14-29.6% of all acute ischemic stroke (AIS) cases. The use of intravenous alteplase, the therapeutic standard, requires identifying time of stroke onset. Recent studies suggest that obstructive sleep apnea (OSA) is an independent risk factor for WUS. This study aims to describe a population of Puerto Rican Veterans with WUS and to evaluate clinical differences between patients WUS and non-WUS (NWUS). Methods: The study was a cross-sectional analysis of all patient records with AIS from April 2018 to July 2019. One hundred forty records were reviewed. Patients who woke up with new AIS symptoms were labeled as WUS. Study variables included demographics, comorbidities, medications, sleep disorders, prior stroke, administration of alteplase and the National Institute of Health Stroke Scale (NIHSS). Results: Among 140 participants predominantly male (98.6%), 27.1% had WUS. The mean age was 75 (range 21-89). NIHSS mean was 5.9. Comorbidities for WUS vs NWUS were as follows: overweight or obese (60% vs 62.6% p=0.667), hypertension (100% vs 95.1% p=0.323), hyperlipidemia (95% vs 93% p=0.999), diabetes mellitus (55.3% vs 67% p=0.212), atrial fibrillation (26.3% vs 24.5% p=0.826), anxiety (36.8% vs 33.3% p=0.697), depression (55.3% vs 51.0% p=0.652), non-smokers (89.% vs 89%), smokers (10.5% vs 11.1%), and prior stroke (34.2% vs 35.3% p=0.905). Insomnia was observed in 42% vs 40% (p= 0.838) and 24% vs 23% (p=0.955) had OSA. Conclusion: There were no significant differences in clinical characteristics between patients with WUS and NWUS in this sample of Puerto Rican Veterans. OSA was less prevalent than previously reported. Lack of recognition of OSA as a risk factor for stroke and under-diagnosis of OSA might explain the study results. Support: